Art Deco and Vienna - Nashchokina, Maria (project baikal, 2019)
The article considers the formation of the Art Deco style in the Viennese architectural school and highlights the role of Josef Hoffman in the emergence of a new stylistic theme formally opposite to Art Nouveau. The article studies the change in the function of decoration in the architectural image through the example of A. Stoclet Palace in Brussels. The relation of Hoffman’s individual artistic language to the development of the Art Deco style was demonstrated in the architecture of the pavilions at the 1925 Paris International Exhibition. Similarity of Art Deco and Art Nouveau was in the origin, in comprehension of the “great style” lasting for almost the entire 20th century.